Longitudinal effects of cognitive behavioral therapy for depression on the neural correlates of emotion regulation. (30th January 2018) - Rubin-Falcone, Harry; Weber, Jochen; Kishon, Ronit; Ochsner, Kevin; Delaparte, Lauren; Doré, Bruce; Zanderigo, Francesca; Oquendo, Maria A.; Mann, J. John; Miller, Jeffrey M.
Abstract: Cognitive behavioral therapy (CBT) is effective for a substantial minority of patients suffering from major depressive disorder (MDD), but its mechanism of action at the neural level is not known. As core techniques of CBT seek to enhance emotion regulation, we scanned 31 MDD participants prior to 14 sessions of CBT using functional magnetic resonance imaging (fMRI) and a task in which participants engaged in a voluntary emotion regulation strategy while recalling negative autobiographical memories. Eighteen healthy controls were also scanned. Twenty-three MDD participants completed post-treatment fMRI scanning, and 12 healthy volunteers completed repeat scanning without intervention. Better treatment outcome was associated with longitudinal enhancement of the emotion regulation-dependent BOLD contrast within subgenual anterior cingulate, medial prefrontal cortex, and lingual gyrus. Baseline emotion regulation-dependent BOLD contrast did not predict treatment outcome or differ between MDD and control groups. CBT response may be mediated by enhanced downregulation of neural activity during emotion regulation; brain regions identified overlap with those found using a similar task in a normative sample, and include regions related to self-referential and emotion processing. Future studies should seek to determine specificity of this downregulation to CBT, and evaluate it as a treatment target in MDD. Highlights: We used an emotion regulation fMRI task to study cognitive behavioral therapy. Participants with major depression scanned pre- and post-treatment. Treatment outcome scales with changes in emotion regulation-dependent BOLD signal. Regions identified have been associated with emotion regulation in normative sample. The findings suggest a possible neural target for future treatment interventions.